2009
DOI: 10.1177/193229680900300613
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control in the Medical Intensive Care Unit

Abstract: Hyperglycemia in the critically ill is a well-known phenomenon, even in those without known diabetes. The stress response is due to a complex interplay between counter-regulatory hormones, cytokines, and changes in insulin sensitivity. Illness/infection, overfeeding, medications (e.g., corticosteroids), insufficient insulin, and/or volume depletion can be additional contributors. Acute hyperglycemia can adversely affect fluid balance (through glycosuria and dehydration), immune and endothelial function, inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
0
16
0
3
Order By: Relevance
“…During the last 10 years an intensified insulin therapy for critically ill patients has been a major issue of discussion. An intensified insulin therapy has been found to be of benefit or of no benefit to patients, depending on the clinical study [36][37][38]. Possibly this discrepancy may be resolved by the assumption that an intensified insulin therapy is beneficial to certain subsets of patients, whereas in other subsets of critically ill patients the risk of hypoglycaemia will outweigh beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 10 years an intensified insulin therapy for critically ill patients has been a major issue of discussion. An intensified insulin therapy has been found to be of benefit or of no benefit to patients, depending on the clinical study [36][37][38]. Possibly this discrepancy may be resolved by the assumption that an intensified insulin therapy is beneficial to certain subsets of patients, whereas in other subsets of critically ill patients the risk of hypoglycaemia will outweigh beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…A fentieken túl a stresszhez kapcsolódó hyperglykaemiában szerepet ját-szik a kritikus betegségekben a tumornekrózis-faktor-α-(TNF-α-) és interleukin-1-(IL-1-) szint emelkedése, amely hozzájárul a kulcsfontosságú perifériás és hepatikus inzulinrezisztencia kialakulásához [2,3,4,5,6,7]. Az intenzív betegellátás és a hyperglykaemia fontos kapcsolatát a Web of Science adatbázisban a témában közölt irodalom mennyisége reprezentálja, amely 2000 óta meredek emelkedést mutat (1. ábra).…”
unclassified
“…Two additional single centers, randomized studies showed a trend towards a higher mortality in the TGC arm (72,73). TGC is strongly associated with an even sixfold-increase in episodes of severe hypoglycemia (glucose levels < 2.2 mmole/l, 40 mg/dl) (20) and, as mentioned before, this state can have dramatically adverse effects such as coma or even death (74). The recent NICE-SUGAR study showed that an intensive glucose control increased mortality among ICU adults, and that an 81-108 mg/dl target was too ambitious and potentially dangerous (12).…”
Section: Approaches On Glycemic Control During the Perioperative Perimentioning
confidence: 99%